Effective approaches to resource management in 3D games on unity - Kiiko, Maksym; Azarenkov, Volodymyr Illich (BoScience Publisher, 2024)
This paper presents research on effective methods for managing 3D resources in the Unity game engine to reduce memory usage and improve game performance. By optimizing 3D models, textures, audio, and code through techniques such as simplifying geometry, compressing assets, and efficient memory management, developers can enhance performance, especially on resource-constrained platforms like mobile devices and virtual reality applications. Practical examples, including the use of Unity's profiling and optimization tools, demonstrate how these methods contribute to creating high-quality, efficient games that meet modern players' expectations.
Keywords: unity; 3D games; resource management; optimization; performance improvement; memory usage; profiling tools; mobile platforms; virtual reality; game development